Integrating Spirituality in Health Science Education: An Empirical Study of University Students and Lecturers - Muriithi Ndereba, Kevin (Christian higher education, 2025)
This research interrogates the integration of spirituality in health science education through a semi-structured survey of 23 nursing students as well as semi-structured surveys and focus group interviews conducted with seven lecturers in the school of health sciences at St. Paul’s University, Kenya. The research acknowledges the way in which the COVID pandemic has foregrounded public health issues such as stress, mental health, and trauma in the specific areas of student self-care, nursing practice, curriculum review, and faculty training and development. Conducted by a theologian and health scientist, this study utilizes an integrative model of faith and science to demonstrate the need for integrating spirituality in health science education within the context of Christian higher education.